Managerial accounting - Hilton, Ronald W. (New York : McGraw-Hill, 1997)
"Mangers in all types of organizations rely heavily on managerial accounting information for decision making, planning, and control. The goal of this text is to acquaint student of management with the fundamentals of managerial accounting. The emphasis throughout the book is on using accounting information in managing an organization. Managerial accounting is intended to be used by student after they have completed a basic course in financial accounting. most of the material in the text can be covered in one semester or one and one-half quarters the book includes enough material, however, to allow an instructor some choice of topics when designing the course. In preparing the third edition of managerial accounting, many features of the first two editions were retained. However; several improvements and changes have made based on the comments of the reviewers, instructors, and students who have been used the text This preface provides a summary of the text key's features and the changes in the third edition."
Includes bibliographical references and indexes.
English text.
Keywords: Managerial accounting